Uma geografia emocional do Nordeste na sala de aula : o sertão de Luiz Gonzaga - Silva, Aline Celestina dos Santos (2023)
Among the different directions that were consolidated throughout the historical and scientific development of Geography, the so-called Humanist strand has enabled research that has a subjective character. As a result of this assumption, Emotional Geography analyzes the geographic space from the emotions, feelings and experiences of the human being in the world where he (coexists) lives. In this context, this research aims to reflect on an Emotional Geography of the Northeast of Brazil in the classroom from the geographic imagination and the songs written and/or sung by Luiz Gonzaga, the King of Baião (1912-1989). For this, we will seek this reflection from the interpretation of Mental Maps. Among the authors who provide theoretical support, it is worth highlighting Furlanetto (2014) by providing a dialogical relationship between emotions and the category place; Andreotti (2013) who addresses Emotional and Cultural Geography in comparison with the rationalist one; Silva (2019) who discusses the importance of emotions in Geography; Torres (2010) showing that landscapes have sounds that contribute to the understanding of the identity of places and individuals who inhabit them; Kozel (2013) pointing out mental maps as sociocultural constructions; Wright (2014) demonstrating the important role of geographic imagination. To this end, pedagogical workshops were held with students from the 7th year of Elementary School II at the Santos Dumont School, located in Cuiabá-MT. The class was chosen precisely because the theme of Brazil's regional divisions is a curricular component of the geography discipline. It can be identified, that the main symbols and meanings that represent the Northeast and the Northeastern, concern their faith, with representation of churches, and their resistance, with the representation of cacti/mandacaru. As for emotional issues, there was a predominance of topophilic aspects, but it was also found distorted understandings about this region.